2022
DOI: 10.3389/fmicb.2022.831272
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome, an Important Factor That Is Easily Overlooked in Male Infertility

Abstract: Humankind has been interested in reproduction for millennia. Infertility, in which male factors contribute to approximately 50%, is estimated to concern over 72 million people worldwide. Despite advances in the diagnosis, medical treatment, and psychosocial management of male infertility over the past few decades, approximately 30% of male infertility is still thought to be idiopathic. Despite emerging advances in the microbiome associated with male infertility have indicated that the microbiome may be a key f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…Sexual selection and reproductive success [69][70][71][72] Sexual performance issues, infertility, conception problems and problems carrying to term have all been linked with dysbiotic reproductive microbiomes.…”
Section: Control Of Offspring Maladies [52-54]mentioning
confidence: 99%
“…Sexual selection and reproductive success [69][70][71][72] Sexual performance issues, infertility, conception problems and problems carrying to term have all been linked with dysbiotic reproductive microbiomes.…”
Section: Control Of Offspring Maladies [52-54]mentioning
confidence: 99%
“…Studies show that infertile men may have elevated levels of ROS and less effective semen antioxidant capacity (Lewis et al, 1997;Subramanian et al, 2018). Wang et al (2022) point out that, despite efforts to identify the causes and develop new approaches to improve male fertility in recent decades, there are still few effective treatments to delay the decline of idiopathic male infertility. Thus, recent studies have evaluated different antioxidant supplementation strategies and their effects on ROS to improve male infertility (Bozhedomov et al, 2017;Kızılay & Altay, 2019;Kopets et al, 2020) and it has been shown that natural antioxidants or vitamin supplements, like vitamins C and E, glutathione, folate, zinc, selenium, carnitine, coenzyme Q10, lycopene, and N-acetyl cysteine, can neutralize free radicals thus improving semen parameters (Bui et al, 2018;Busetto et al, 2018;Gamidov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… Wang et al . (2022) point out that, despite efforts to identify the causes and develop new approaches to improve male fertility in recent decades, there are still few effective treatments to delay the decline of idiopathic male infertility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a convincing body of evidence suggesting the potential of short ejaculatory abstinence in improving the sperm quality, its impact on the changes in the bacterial profiles of semen have been by and large overlooked. In the past, samples collected from the reproductive tract of clinically healthy males were considered free from bacteria, which has resulted in the male reproductive microbiome not being well described [ 19 ]. Yet, recent studies have found that bacteriocenoses are a normal part of the male urogenital system and body fluids, including semen and urine [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%